Nationalism In The Quran - Sembiring, Raja Margana; Nasution, Muhammad Roihan; Junaidi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Nationalism is an ideology that emphasizes the importance of individual and group identification with a particular nation or state, often promoting values of togetherness, sovereignty and national identity. This ideology has deep historical roots, developing along with the process of forming modern nation-states and the struggle for independence from colonial or imperialist powers. This research is a qualitative research with a type of literature study research where the sources are taken from the Al-Qu'an and reference books related to the research. The results of this study explain about nationalism based on the mufassir's point of view. Then explain the verses related to nationalism.